An Interpretation of the So-called Paraffin Dirt of the Gulf Coast Oil Fields ? Discussion (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
W. E. WRATHER, Wichita Falls, Tex. (written discussion*).-The appearance of Mr. Brokaw?s with-the chemical composition of "paraffin dirt" will be welcomed by oil geologists who have worked in the Gulf Coast district. It is to be hoped that it will lead to a discussion of the subject which will throw some light on the relation this peculiar substance bears to the occurrence of oil deposits. The problem of locating oil pools in advance of drilling is at the best a very intangible matter in the district along the Gulf Coast, and it is therefore desirable to make the most of any clew which may be of the least assistance to this end. Geologists have been familiar with "paraffin dirt" for a number of years, and have informally discussed its value as a surface indication of oil. But doubtless owing largely to the fact that they have been unable to define its exact composition, very little information has appeared in print on the subject. The presence of this baffling and somewhat indeterminate substance is now quite generally accepted as one of the most reliable indications of a gas seepage. The question is whether paraffin dirt necessarily indicates that the escaping gas is an emanation from an oil deposit, or whether it merely indicates that marsh gas (urethane) has here escaped from its source in "the abundant decomposing vegetation entombed in the sediments of the old Mississippi Embayment, and the Gulf Coastal Plain. The presence of this material has been relied upon to a great extent, both by oil producers and geologists, in the location of wildcat wells, since the discovery that it was associated with gas seepages. It is quite true that other surface indications were often present at such localities, but if, in addition, paraffin dirt could be found in the vicinity, this fact was accepted as the final justification for drilling a test well, despite the fact that no one seemed to understand its chemical composition or to know why it should be associated with oil. In fact, for a long time it has generally been accepted that the name is a misnomer, that very little, if any, paraffin is present in it, or, for that matter, any other known fraction of crude oil.